Frequently Suspected, Rarely Confirmed: The Complex Diagnostic Journey of Adult-Onset MELAS—Clinical Evaluation and Cost Implications - Sebastian Finkener; Arkady Ovchinnikov; Ronald Bauer; Michael Diepers; Markus Gschwind (Clinical and Translational Neuroscience)
Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is a rare mitochondrial disorder primarily presenting in pediatric patients, with onset after 40 years being exceptionally rare (1–6%). Here, we report a complex diagnostic journey of a 47-year-old male presenting with new-onset seizures, hemiparesis, and neurocognitive deficits. Initial work-up, including MRI, CSF analysis, and extensive antibody screening, yielded inconclusive results, prompting differential considerations such as autoimmune encephalitis and neoplastic conditions. Finally muscle biopsy findings, coupled with genetic confirmation of the m.3243A>G mutation in the MT-TL1 gene, ultimately established the diagnosis of MELAS. This case depicts the atypical presentation of adult-onset MELAS without initial lactic acidemia, diabetes, or hearing impairment. The prolonged diagnostic process underscores the challenges of identifying rare diseases under today’s financial and administrative constraints. Still ee emphasize the importance of comprehensive diagnostics in rare cases to advance generall understanding and improve future patient outcomes, also amidst resource limitations.